Surat Keterangan Hak Waris Dalam Ketentuan Hukum Waris Nasional - Sovia Febrina Tamaulina Simamora (Visi Sosial Humaniora, 2022)
This research was discussing the regulation about Inheritance Rights certificate, About Inheritance Specification form are not made out in the legal form, so the certificate of inheritance right including by the privat document (subscribed deeds). The Legal form about Inheritance Right certificateÂ  just regulated in article 111 (1) c he Regulated by minister of Agrarian number 3/1997 aboutÂ  implementation of the provisions of government number 24/1997 on land Registration (PMNA 03/1997), which is about the officials authorized to issue Descrcription Inheritance Right certificate based on group population and the implementing the regulations in society for a legal evidence in the transfer of rights due to inheritance. The research was conducted using the normative research is library research on secondary data in the fields of law, based on the systematic regulations in Indonesia. In the processing, analysis and conctructionof qualitative data, which are mono-disciplianary, research typologies problem identification and problem solution by prescriptive-explanatory achieve solution to solve problems concerning inheritance issued the official was authorized, also from the point of application to a problem focused, also from the point of application to a problem focused research to provide legal certainty, the inheritance right certificate made by each other. And the efforts should be made to ensure legal certainty regarding the accuracy of the validity of the inheritance certificate is to formulate a legal product regarding the form and content of the inheritance certificate which is to accommodate the needs of the heirs so that the effectiveness of the proof is not confusing and on target.